Hierarchical Self-Assembly of Proteins Through Rationally Designed Supramolecular Interfaces - Sun, Hongcheng; Li, Yan; Yu, Shuangjiang; Liu, Junqiu (Frontiers in Bioengineering and Biotechnology, 2020)
With the increasing advances in the basic understanding of pathogenesis mechanism and fabrication of advanced biological materials, protein nanomaterials are being developed for their potential bioengineering research and biomedical applications. Among different fabrication strategies, supramolecular self-assembly provides a versatile approach to construct hierarchical nanostructures from polyhedral cages, filaments, tubules, monolayer sheets to even cubic crystals through rationally designed supramolecular interfaces. In this mini review, we will briefly recall recent progress in reconstituting protein interfaces for hierarchical self-assembly and classify by the types of designed protein-protein interactions into receptor-ligand recognition, electrostatic interaction, metal coordination, and non-specific interaction networks. Moreover, some attempts on functionalization of protein superstructures for bioengineering and/or biomedical applications are also shortly discussed. We believe this mini review will outline the stream of hierarchical self-assembly of proteins through rationally designed supramolecular interfaces, which would open minds in visualizing protein-protein recognition and assembly in living cells and organisms, and even constructing multifarious functional bionanomaterials.